Confessions of an inadequate researcher: space and supervision in research with learning disabled children - von Benzon, Nadia (Social & cultural geography, 2017)
Location is often at the fore of decision-making regarding fieldwork and choice of methods. However, little research has directly discussed the importance of the choice of site in the production of research data, particularly concerning the way that different relationships will manifest between researcher and participant in different spaces. Site may be particularly important in research with (learning disabled) children, as research location is intertwined with the level of caregiving required from the researcher, and the sorts of surveillance the research engagement may be subject to. This paper draws on research with learning disabled 6-16-year olds that took place in homes, schools and the outdoors, in a variety of microgeographical locations from bedrooms to nature reserves. This paper reflects on the challenges, including the very 'worst' research moments, occurring in the different research environments. Whilst the research was carried out with learning disabled children and young people, the discussion has implications for research with non-disabled children and 'vulnerable' participants more broadly.